El rol del notario en la autenticidad de documentos privados - Flores Valle, Arlette Carolina (2026)
The role of notaries in the authentication of private documents within the Ecuadorian legal framework is crucial to ensuring legal certainty in protecting the wishes of the parties involved. Therefore, the objective of the research is to analyze the role of the notary in the authentication of private documents, identifying its importance in legal certainty and its impact on the prevention of fraud and legal conflicts in order to present objectivity in the treatment of information, which sets fundamental parameters for the best treatment of issues concerning the protection of private documents. The methodological framework provides a qualitative perspective, since, as there are pre-established parameters, it also presents doctrinal analysis and interviews that are linked to how the work is carried out in the notary offices of Baños and Guamote, which showed a comparative study highlighting that in the Guamote notary office, control of private documents is delegated, whereas in the Baños notary office, the notary handles the documents personally. The results show that the notary's office not only grants formal validity to documents, but also seeks to prevent conflicts and strengthen public trust in the awareness of the population, thus analyzing the systems used by notary offices nationwide. It is concluded that the notary is the public figure who provides legitimacy in the control of private documents.